Predictors of recidivism among halfway house residents - Walsh, Charles L. (American journal of criminal justice, 1990)
This study concerns client success or failure while residing in a halfway house for adult offenders. As with some other studies, failure or recidivism is defined in this analysis as behavior that results in removal from the facility and subsequent incarceration. This quantitative case study of one treatment facility in Tennessee utilized case records on the population of clients from 1981 through 1987 (N = 75). A number of hypotheses were developed and tested with both bh/ariate and multivariate methods. Results indicated that, at least in this halfway house, those residents who had experienced two or more prison terms and who had most recently been convicted for a violent crime were most likely to recidivate while in the facility. Other substantively significant factors were alcohol use, religious attendance, and the experience of mental health counseling. Programmatic implications of these results are discussed.